Effects of apple pomace as a sucrose substitute on the quality characteristics of compound chocolate and spread - Buker, Mine; Angin, Pelin; Nurman, Nesil; Rasouli Pirouzian, Haniyeh; Akdeniz, Esra; Toker, Omer Said; Sagdic, Osman; Tamturk, Faruk (WILEY, 2021)
The purpose of the this study was to determine the effects of dried apple pomace (DAP) as a partial replacer for sucrose on the compound chocolate and chocolate spread formulation. The DAP concentrations changed between 4 and 20 g/100 g. The results indicated that with the increase of DAP in the chocolate samples, particle size, hue angle, and total amount of phenolic substances of samples increased. However, the hardness, color parameters, and overall acceptance decreased. Furthermore, firmness and spreadability of spreads were evaluated between 4.04-5.98 N and 1.92-3.05 N/mm, respectively. Presence of polyphenols and dietary fiber indicated that this by-product could be used as a healthy ingredient in chocolate and spread formulation to partially replace sucrose. However, during the processing of the DAP; the initial particle size of pomace can be further reduced by increasing the grinding speed, time, or number of grinding steps. Practical applications The application of fruit by-products is increasing rapidly in the preservation of fruits because of being healthy for consumers. Apple pomace is an important by-product to enhance the nutritional quality of compound chocolate and chocolate spreads. The antioxidant potential of apple pomace makes it advantageous for the chocolate and its derivatives without negatively affecting the quality of the final product.
Keywords: PARTICLE-SIZE DISTRIBUTION; DIFFERENT BULKING AGENTS; DIETARY FIBER; RHEOLOGICAL PROPERTIES; TEXTURAL PROPERTIES; MILK CHOCOLATE; ANTIOXIDANT; POLYPHENOLS; EXTRACTS; DOUGH; Food Science & Technology